Adulthood temperament and educational attainment: A population-based cohort study. (December 2015) - Mullola, S.; Hintsanen, M.; Elovainio, M.; Pulkki-Råback, L.; Lipsanen, J.; Josefsson, K.; Lehtimäki, T.; Raitakari, O.T.; Keltikangas-Järvinen, L.
Abstract: The aim of the study was to examine the associations of temperament traits and temperament profiles (i.e., the combinations of multiple traits) with adulthood educational attainment. The participants were 837 women and 592 men from a population-based cohort study. Temperament was assessed with the Temperament and Character Inventory (TCI) based on the Psychobiological Model of Temperament and Character. Analyses were conducted with linear regression analyses and with analysis of variance (ANOVA). In both genders, high harm avoidance was associated with lower educational attainment. High persistence among women and high reward dependence among men were related to higher educational attainment. Novelty seeking was not associated with educational attainment in either gender. Among men explosive and methodical temperament profiles were associated with lower educational attainment while reliable and passionate temperament profiles were associated with higher educational attainment. Temperament may play an important role in lifelong learning and academic performance over different developmental transitions. Highlights: Temperament is associated with adulthood Educational attainment. Three temperamental partly overlapping dimensions seem to pass over different developmental transitions. The associations between temperament and Educational attainment are gender-specific. Temperament-conscious education needs to be taken into account in teacher training. This enables teachers to identify the specific risks for difficulties in early educational pathways.